Power solution of the cosmological model of the Valecki type - Аймухамбетова, А; Разина, О; Цыба, П; Мейрбеков, Б (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
In this article, we consider a model that includes fermion, scalar, and vector fields that interact through the Yukawa potential. It is shown that their interaction, which occurs together with the Friedmann-Robertson-Walker metric, can serve as a source of transition in the accelerated-delayed period in the early Universe and the modern accelerated mode. The role of the fermion and scalar fields as sources of the accelerated mode at the early and late stages of the Universe development is considered. For our model, a system of equations of motion is found corresponding to the action. Found kinematic parameters that confirm the accelerated expansion of the universe. Built graphics for the energy density ρ and pressure p .